A comparison of traditional and weekly undulating periodized strength training programs with total volume and intensity equated - Apel, J. M.; Lacey, R. M.; Kell, R. T. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to compare the training adaptations attained during 12 weeks of traditional (TD) and weekly undulating (WUD) periodized strength training. Forty-two recreationally active men (age = 22 ± 2.3 years) were randomly assigned to 1 of 3 groups: control (C) (n = 14), TD (n = 14), or WUD (n = 14). Ten-repetition maximum (10RM) laboratory testing was carried out for the free weight back squat and the free weight flat bench press at baseline, week 8, and week 12. The subjects trained 3 d/wk (approximately 135 min/wk) from weeks 1 to 2 and 4 d/wk from week 3 to week 12 (approximately 180 min/wk). The TD and WUD groups trained using a periodized strength program with all program variables controlled (e.g., volume and intensity). The independent variable was the manipulation of intensity. The TD group used a linear increase in intensity, whereas the WUD group had a varied intensity. The results showed that both the TD and WUD groups made significant (p = 0.05) increases in strength at weeks 8 and 12, but by week 12, the TD group was significantly (p = 0.05) stronger than the WUD group. These results indicate that TD periodization with a linear increase in intensity was more effective at eliciting strength gains than WUD periodization with a varied intensity. The differences in strength gains between the TD and WUD groups may be related to extended periods of muscle soreness and fatigue that were present in the WUD group but not in the TD group. Thus, during long-term training, individuals may benefit more from TD periodized programs because there may be less muscle soreness and fatigue to disrupt practice and training.